Idiopathic Macular Hole yang Terjadi setelah Pembedahan Katarak dengan Teknik Fakoemulsifikasi: Laporan Kasus - Nursalim, Ade John; Sumual, Vera (UNIVERSITAS SAM RATULANGI, 2019)
Abstract: Macular hole (MH) up to now has an unknown exact etiology or mechanism behind its formation. It can be formed post cataract surgery with phacoemulsification technique with a relatively small probability. We reported a male of 74 years old who came with diminished visual acuity of his left eye three months after cataract surgery with phacoemulsification procedure. In ophthalmologic examination we found the visual acuity of the right eye was 6/60 and of the left eye was 2/60. Fundoscopy of the left eye revealed a depression in fovea region with estimated size of 500 Î¼m. Optical coherence tomography (OCT) examination resulted in intraretinal fluid with multiple cyst appearance in retinal layers associated with retinal thickening. Based on anamnesis, physical examination, and imaging examination, the diagnosis of this patient was stage 3 macular hole with vitreomacular traction. Management of this patient was pars plana vitrectomy (PPV). One week after PPV, the patient gained a remarkable visual acuity improvement (6/12), albeit, there was still slight metamorphosia.Keywords: macular hole, cataract surgery, phacoemulsificationÂ Abstrak: Macular hole (MH) hingga saat ini masih tidak diketahui penyebab pastinya ataupun mekanisme dasar terjadinya MH. Penyakit ini juga dapat terbentuk pasca operasi katarak dengan teknik fakoemulsifikasi meskipun dengan probabilitas yang relatif kecil. Kami melaporkan sebuah kasus MH pada seorang laki-laki berusia 74 tahun dengan keluhan pandangan kabur pada mata kiri 3 bulan setelah operasi katarak (teknik fakoemulsifikasi). Pada pemeriksaan oftalmologi didapatkan tajam penglihatan mata kanan 6/60 dan mata kiri 2/60. Pada pemeriksaan lanjut mata kiri menggunakan funduskopi ditemukan cekungan pada bagian fovea dengan ukuran sekitar 500 Î¼m. Pemeriksaan dengan OCT mendapatkan intra-retinal fluid dengan gambaran kista multipel pada lapisan retina disertai penebalan retina. Berdasarkan anamnesis, pemeriksaan fisik, dan imaging, diagnosis pada pasien ini ditegakkan sebagai macular hole stadium 3 dengan vitreomacular traction pada mata kiri. Tata-laksanayang dilakukan ialah vitrektomi pars plana (VPP). Satu minggu setelah VPP, tajam penglihatan pasien membaik secara drastis menjadi 6/12 walaupun masih terdapat metamorphopsia ringan.KataÂ kunci: macular hole, operasi katarak, fakoemulsifikasi